THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION WITH TRADITIONAL GIFT-GIVING USING A MODERN APPROACH AT KREASI ISTANA WINGKING - Ririn Handayani; Amin Silalahi; Harmawan Teguh Saputra (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to analyze the effect of service quality on customer satisfaction in traditional gift-giving (seserahan) services with a modern approach at Kreasi Istana Wingking. The growing demand for customized, aesthetically enhanced seserahan services underscores the importance of maintaining high service standards to ensure customer satisfaction and competitiveness in the creative services industry.Methods: This research employs a quantitative explanatory approach involving 35 respondents selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire developed based on SERVQUAL dimensions and customer satisfaction indicators. The instrument was tested for validity and reliability, and the data were analyzed using simple linear regression after satisfying classical assumptions, including normality, multicollinearity, and heteroscedasticity tests.Results: The findings indicate that service quality positively and significantly influences customer satisfaction. Customers generally provided very positive evaluations of the services received, indicating that reliability, responsiveness, assurance, empathy, and tangible aspects play an important role in shaping satisfaction in traditional–modern seserahan services.Conclusion and Suggestion: It can be concluded that improving service quality is essential for enhancing customer satisfaction. Service providers are encouraged to maintain consistent service standards, improve communication clarity, ensure timeliness, and provide personalized attention to strengthen customer trust and long-term business sustainability. Keywords: Customer Satisfaction, , Kreasi Istana Wingking, Service Quality, SERVQUAL, Traditional–Modern Gift Service